ISSP 1999 - Social inequality III: Sweden - Edlund, Jonas; Svallfors, Stefan (Umeå University, 2009)
This survey is the Swedish part of the 1999 'International Social Survey Program'. ISSP is an ongoing program of cross-national collaboration. Formed in 1984, the group develops topical modules dealing with important areas of social science as supplements to regular national surveys.

The topic of 1999 was 'Social inequality'. In this survey the respondents had to give their opinions on equality of income, wealth, and opportunity. Respondents were asked to give an estimate of average monthly income of selected occupational groups and inform on a justified income for the members of these occupational groups from the point of view of the respondent. The respondents also had to give their judgement on total taxation for recipients of high, middle and low income. Other questions dealt with perceived social conflicts in the country; different criterias for establishing work pay; attitudes towards people receiveing different kinds of social benefits. Socio-economic background information include occupation, trade union affiliation, education, housing, income, marital status, spouse's occupation, income, number of children, citizenship of parents, and political preferences.

Purpose:

ISSP aims to design and implement internationally comparable attitude surveys. The study in 1999 investigating Social Inequality.

Detta är den svenska studien inom det internationella forskningsprojektet ISSP. Temat för studien 1999 är ” Social Inequality”. Detta är tredje gången studien genomförs på det här temat och har sedan genomförts ytterligare en gång på samma tema (SND 0875).

International Social Survey Program, ISSP, är ett globalt forskningsprojekt som har till uppgift att konstruera och genomföra internationellt jämförbara attitydstudier. Sedan 1985 har attityddata årligen samlats in och utgör nu en databas som är fritt tillgänglig för forskarsamhället. I dagsläget är 48 länder, från sex olika världsdelar, involverade i projektet. Genom bredden av medlemsländer skapas möjlighet till jämförelser i flera dimensioner. Det finns möjligheter att både jämföra länder som har en likartad samhällsstruktur och historia, och länder som skiljer sig påtagligt från varandra.

Sverige har varit medlem i ISSP sedan 1992 och det är Sociologiska intuitionen vid Umeå universitet som är huvudman för studierna i Sverige.

Sedan starten 1985 har attityder från flera olika områden undersökts. Vissa områden har återkommit genom åren, vilket gör det möjligt att även jämföra dem över tid.

Syfte:

ISSP har som syfte att konstruera och genomföra internationellt jämförbara attitydstudier. Studien för 1999 undersöker åsikter ojämlikhet I Sverige.
ISSP 1999 - Åsikter om ojämlikhet i Sverige
Keywords: employment; anställning; economics; ekonomi; social welfare; social välfärd; CORS; CORS; Equality, inequality and social exclusion; Jämlikhet, ojämlikhet och socialt utanförskap; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Sociology; Sociologi